Better together - George, K. (Kallie), 1983-; Graegin, Stephanie (Los Angeles : Disney/Hyperion, 2018)
Spring is here and the animal staff at the Heartwood Hotel are busy arranging a series of festivals and competitions to drum up business and to show its patrons that Heartwood is the greatest hotel in Fernwood Forest.
4.0
3-6
600L
Keywords: Hotels -- Juvenile fiction; Forest animals -- Juvenile fiction; Spring -- Juvenile fiction; Hotels, motels, etc. -- Fiction; Forest animals -- Fiction; Spring -- Fiction